Aplicação do método Phitoscreening para determinação de hidrocarbonetos clorados no município de Porto Feliz - SP - Ferraz, Daniela Martinez Figueiredo [UNESP] (2014)
When tree roots come in contact with the unsaturated zone and shallow groundwater contaminated by volatile organic compounds, these compounds are transported by xylem vessels and enter on the flow of perspiration trees. Thus, the sampling method of the bark of trees is a research tool that indicates the presence of these contaminants in the subsurface and is called phytoscreening. The objective of this work was to verify the applicability and effectiveness of phytoscreening method for investigating and determining contamination plumes in areas impacted by chlorinated organic compounds. Samples of tree trunks were collected in a contaminated area in Porto Feliz, Brazil. A scan was performed in most of the trees present in the area and the surrounding area, were also collected vegetative parts of trees for identification of species. To collect tree colors used a tool which consists of a hollow drill suitable for drilling and an extractor to remove the sample from inside the drill. After drilling, the samples were transferred to vials and sealed . In this study we tested different chemical analysis device for the detection of contaminants in tree cores. Among them the GC- TID and the HS- GC- MS laboratory and field. The samples were subjected to laboratory analysis and headspace sampler coupled to mass spectrometry (HS-GC-MS) gas chromatography. After treatment of the data, it was possible to making maps of the extent of the contamination plume and the spatial distribution of different organic contaminants. Different chlorinated organics were detected by the method phytoscreening as chloroform, trans -1,2-dichloroethene, cis-1,2-dichloroethene, carbon tetrachloride, 1,2-dichloroethane, trichloroethene, tetrachloroethene, 1,1,2-trichloroethane and 1,1,2,2-tetrachlorethane. All equipment used in the testing of samples confirmed the existence of contamination at the site and were efficient in the use of the method for screening....